ADVANCED ENCRYPTION STANDARD (AES) IMPLEMENTATION EFFICIENCY USING JAVA AND NODE.JS PLATFORMS - Ugwunna, Charles Okechukwu; Okimba, P. E.; Alabi, O. A.; Orji, E. E.; Olowofeso, E. O.; Ayomide, S. O. (FUDMA Journal of Sciences, 2024)
The rapid advancement of communication technologies, such as satellite networks, mobile, internet, and terrestrial communications, has created an urgent need to protect sensitive data from potential attacks. This is particularly crucial as photos transmitted through unreliable channels may contain sensitive or confidential information. This study evaluates the effectiveness of the Advanced Encryption Standard (AES) algorithm implemented in Java and Node.js, focusing on their performance in data encryption and decryption. The research employs AES in Cipher Block Chaining (CBC) mode, using 128-bit keys for Java and 256-bit keys for Node.js. It utilizes the Java Cryptography Architecture (JCA) and Java Cryptography Extension (JCE) to create an optimized runtime environment with advanced cryptographic libraries. The result indicate that Java's AES-128 implementation is more efficient than Node.js's AES-256, particularly in terms of speed and data processing capabilities as seen in figure 11 taking Java 2.00ns to encrypt and decrypt before the Node.js algorithm that couldn’t complete the process but remain at 0.75ns. Suggesting that specific use case and requirements should be considered when choosing between the two platforms for AES encryption. Java generally outperforms Node.js in efficiency, but Node.js provides essential cryptographic functions through its built-in 'crypto' module. Overall, the research underscores the advantages of using the AES algorithm across these platforms while demonstrating the varying performance characteristics between them.
Keywords: Encryption; Decryption; Advanced Encryption Standard (AES); Cryptography